Avaliação dos parâmetros abióticos e caracterização do Mesozooplâncton em um viveiro de cultivo de Litopenaeus vannamei (BOONE, 1931) em Curuçá, Pará, Brasil - SILVA, Rafaela Barros (2020)
The fast development of the commercial activity from shrimp creation in important tropical areas of the world have been accompanied by the growth concerns about its environmental sustainability, generating the necessity to know the physical, chemical and biological characteristics of ponds, avoiding risks of environmental damages.This study aims to characterize the physico-chemical and biological quality of water from two points within a pond in a creation farm of marine shrimp Litopenaeus vannamei (BOONE, 1931), which operates in an intensive system, and at two points near the estuary. The research was done in the Farm NossaSenhora de Fátima (Curuçá,-Pará). It was measured the temperature, pH, salinity, electrical conductivity, dissolved oxygen and it was made a collect in order to analyze nutrients, relative abundance, frequency of occurrence, density, diversity and equitability. The pH was in agreement with the Conama Resolution, as well as the dissolved oxygen with the exception of point CAE. The nitrate, ammonium and nitrite nutrients were not in accordance with the IMO. In this work the composition of the zooplankton community comprised 46 fees but the Copepoda is the most abundant group observed at all points studied. Oithona nana, Oithonahebes, Parvocalanuscrassirostris, copepod nauplii andcopepoditoharpacticoids were the species responsible for this abundance. In addition to contribute with abundance these species and Miraciaefferata, Euterpinaacutifrons, copepoditocopepoditoCalanoida and Cyclopoida were found with a great frequency in collection places. The density was represented by genre Oithona species mainly by Oithona nana. The diversity values to the zooplankton showed higher rates at points near the estuary and the equitability values index showed higher in points inside the pond.